Association of sleep duration and sleep disorders with post-stroke depression and all-cause and cardiovascular disease mortality in US stroke survivors: results from NHANES 2005–2018 - Weirong Chen; Yingying Shen; Shina Song; Xiaofeng Li (European Journal of Medical Research)
Abstract Background Sleep disturbance is a common concern among stroke survivors, yet the association of sleep duration and sleep disorders with post-stroke depression and all-cause and cardiovascular disease (CVD) mortality remains elusive. We aimed to explore these associations using data from the National Health and Nutrition Examination Survey (NHANES). Methods Adult stroke survivors from NHANES 2005–2018 were included. Sleep information and stroke diagnoses were derived from self-reports on relevant questionnaires. Mortality data were collected by prospectively matching to the National Death Index. Multivariate logistic regression and Cox proportional hazards regression were used to explore these associations and calculate the odds ratio (OR) and hazard ratio (HR), respectively. Results A total of 1101 stroke participants were included. In the fully adjusted model, sleep disorders were associated with increased odds of post-stroke depression (OR 2.689, p = 0.0146). Sleep duration was inversely associated with the odds of post-stroke depression; compared to normal sleep duration, short sleep duration was associated with increased odds of post-stroke depression (OR 2.196, p = 0.0059), whereas long sleep duration was not (p = 0.1435). Sleep disorders were associated with CVD mortality (HR of 1.948, p = 0.026) but not all-cause mortality (p = 0.224) in stroke survivors. Sleep duration was positively associated with all-cause mortality in stroke survivors (HR 1.075, p = 0.042); however, neither short nor long sleep duration was associated with mortality compared to normal sleep duration. Restricted cubic spline modeling suggested that sleep duration was nonlinearly and linearly associated with post-stroke depression and all-cause mortality, respectively. Age influenced the association between sleep disorders and CVD mortality in stroke survivors. Conclusions Sleep disorders and short sleep duration were associated with increased odds of post-stroke depression, whereas sleep disorders were associated with increased CVD mortality in stroke survivors. These findings underscore that achieving normal sleep duration and improving sleep disorders may reduce the odds of post-stroke depression and mortality.